Zoonotic pathogen seroprevalence in cattle in a wildlife–livestock interface, Kenya - Nthiwa, D.; Alonso, Silvia; Odongo, D.; Kenya, E.; Bett, Bernard K. (Springer, 2019)
A cross-sectional study was conducted to determine the seroprevalence of Brucella spp. and Leptospira spp. and risk factors of exposure in cattle in three zones with varying land use types and wildlife–livestock interactions. Five villages were selected purposively; two in areas with intensive livestock–wildlife interactions (zone 1), another two in areas with moderate livestock–wildlife interactions (zone 2) and one in areas where wildlife–livestock interactions are rarer (zone 3). Sera samples were collected from 1170 cattle belonging to 390 herds in all the zones and tested for antibodies against Brucella abortus and Leptospira interrogans serovar hardjo using ELISA kits. Data on putative risk factors for seropositivity of these pathogens in cattle were collected using a questionnaire. The overall apparent animal-level seroprevalence of brucellosis and leptospirosis was, respectively, 36.9% (95% CI 34.1–39.8) and 23.5% (95% CI 21.1–26.0). Brucella spp. seroprevalence was higher in zone 1 than in zones 2 and 3 (χ2 = 25.1, df = 2, P < 0.001). Zones 1 and 2 had significantly higher Leptospira spp. seroprevalence than zone 3 (χ2 = 7.0, df = 2, P = 0.029). Results of multivariable analyses identified animal sex (female) and zones (high interface area) as significant predictors (P < 0.05) of animal-level seropositivity of Brucella spp. For Leptospira spp., important predictors of animal-level seropositivity were animal sex (female), zones (moderate interface area) and herds utilizing a communal grazing reserve. The seroprevalences of Brucella spp. and Leptospira spp. in cattle were higher in areas with moderate to high wildlife–livestock interactions than those with rare interactions.